The book you're not supposed to have - Pastis, Stephan (Pastis, Stephan. Timmy Failure, 2019)
Timmy Failure, a boy who wanted to be a detective, relates the story of how he got banned from detective work--he didn't deserve it, it was a conspiracy of buffoons. This is Timmy's private record, and if it gets out, he will certainly be grounded for life.